2022
DOI: 10.3390/jcm11206166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy Duration of Topical Therapies in Eyes with Primary Open-Angle Glaucoma

Abstract: Background: To investigate the efficacy interval of the topical therapies available for primary open-angle glaucoma (POAG) and the ocular and systemic features potentially associated. Methods: This retrospective study included 190 patients with POAG undergoing first topical therapy, throughout a follow-up of 15 years. The patients started one topical intraocular pressure (IOP)-lowering drug within single molecules such betablockers, prostaglandin or dorzolamide, or fixed combinations such as betablockers + pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Lanza, M et al (2022) 9 showed an accurate evaluation of the glaucomatous patient with POAG is crucial to selecting a proper IOP-lowering regime, in agreement with the most relevant international guidelines. A treatment selected with the awareness of the molecule interval of efficacy, indeed, would provide an adequate IOP reduction along with avoiding unexpected VF damage progressions and a concomitant reduction of quality of life.…”
Section: Patientsmentioning
confidence: 68%
“…Lanza, M et al (2022) 9 showed an accurate evaluation of the glaucomatous patient with POAG is crucial to selecting a proper IOP-lowering regime, in agreement with the most relevant international guidelines. A treatment selected with the awareness of the molecule interval of efficacy, indeed, would provide an adequate IOP reduction along with avoiding unexpected VF damage progressions and a concomitant reduction of quality of life.…”
Section: Patientsmentioning
confidence: 68%